2017
DOI: 10.1177/0950017017706305
|View full text |Cite
|
Sign up to set email alerts
|

Labour Market Attachment Following Major Workforce Downsizings: A Comparison of Displaced and Retained Workers

Abstract: In plant downsizings, attention tends to be paid to displaced workers, while the retained are considered ‘fortunate survivors’. Exploiting a comprehensive Finnish employee-employer dataset, this study examines both displaced and retained workers and compares their seven-year labour market attachment after downsizing. Advanced statistics, including trajectory analysis, are used to identify groups characterized by ‘immediately weakening’, ‘gradually weakening’ and ‘strong’ employment. Workers displaced in major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
5
0
3
Order By: Relevance
“…Those displaced during the recession of the early 1990s suffered from a substantial and persistent loss of earnings, and the effect of displacement was very heterogeneous and strongest at the lower end of the earnings scale (Korkeamäki & Kyyrä, 2014). Studies applying trajectory analyses also demonstrate differentiation in the re-employment of displaced workers; the share of those who assume the trajectory of stable employment was quite high (Jolkkonen et al, 2014), although not as high as the corresponding share of employees who retained their positions following downsizings (Jolkkonen et al, 2017).…”
Section: Introductionmentioning
confidence: 90%
“…Those displaced during the recession of the early 1990s suffered from a substantial and persistent loss of earnings, and the effect of displacement was very heterogeneous and strongest at the lower end of the earnings scale (Korkeamäki & Kyyrä, 2014). Studies applying trajectory analyses also demonstrate differentiation in the re-employment of displaced workers; the share of those who assume the trajectory of stable employment was quite high (Jolkkonen et al, 2014), although not as high as the corresponding share of employees who retained their positions following downsizings (Jolkkonen et al, 2017).…”
Section: Introductionmentioning
confidence: 90%
“…Other studies have pointed out that even when labour market characteristics are accounted for, women and minorities are more likely to be displaced due to outright discrimination (Couch and Fairlie 2010;Wilson and McBrier 2005). Lastly, Jolkkonen et al (2018) show that women's chances of re-employment are lower than men's and that women are more likely to leave the labour force when displaced. In this context, a voluntary redundancy plan might offer women the possibility to avoid the higher risk of displacement and lower chance of re-employment.…”
Section: Introductionmentioning
confidence: 92%
“…However, the impact of gender remains unclear because it depends on the workers' level of educational attainment and on the period considered after their displacement. For example, men appear to be more likely to be displaced than women, but women lose more in terms of career stability and income in the long run (Kuhn 2002) and are more likely to leave the labour market and enter domestic work (Jolkkonen et al 2018;Snorradóttir et al 2015;Foster et al 2019;Paulsen et al 2005). Regarding non-displaced workers, the literature has shown that certain types of restructuring (mergers, acquisitions and spin-offs) create new opportunities for qualified women in management, although women may never access top positions (Halford and Savage 1995;Woodall, Edwards and Welchman 1997;Pochic and Guillaume 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The analysis could have been further refined by considering the impact of business cycles and specifying the wage and revenue analysis. Although a cyclical and time effect is crucial, we have not included those here, as they were analyzed in our previous studies (Jolkkonen et al 2017a(Jolkkonen et al , 2017b.…”
Section: Strengths and Limitationsmentioning
confidence: 99%